Tracing culture in children's thinking: a socioecological framework in understanding nature (Rastreando la cultura en el pensamiento infantil: una socioecología para comprender la naturaleza). Issue 2 (2nd April 2020) - Taverna, Andrea S.; Medin, Douglas L.; Waxman, Sandra R.
ABSTRACT: There is considerable agreement that cognitive development is shaped by culture. Less clear, however, is the mechanism by which culture exerts its influence as cognition unfolds. Prior work has primarily focused on culture as a species-specific medium of cognitive development or as an explicative factor of cognitive capacities. Here we describe a more recent alternative, the culture-as-ecosystem approach . In this view, concepts are embedded within epistemological orientations providing pervasive, widely distributed framework theories that organize people's knowledge, learning and behaviour. To illustrate the promise of this approach, we review new evidence about how the Wichi, an indigenous population from the Chaco region in North Argentina, reason about hunhat lheley (inhabitants of the earth). By adopting the culture-as-ecosystem approach, we identified a distinct socioecological framework, undocumented elsewhere. This framework, evidenced in young children and adults, is well aligned with Wichi epistemology. We hope that highlighting the theoretical promise and empirical power of the culture-as-ecosystem approach will offer new insights into the intriguing interface between culture and cognition in development.